The Potential Role of Satellite Remote Sensing for Tropical Forest Surveys - Singh, Ashbindu (Indian Forester, 1987)
Remote sensing is the acquisition of information about an object without physical contact. Some of the commonly used remote sensing systems in forestry are-aerial photography, multispectral scanner and rader. Aerial photographs have been utilised in tropical forestry mostly for the stratification of forest types. Multispectral scanner (MSS) system observe the scene under the aircraft or satellite platform in a number of spectral wavebands. The most widely used MSS systems for vegetation studies bave been on board tbe Landsat series of satellites. Landsat data provide a synoptic view and repetitive coverage of large area. Landsat imagery have been applied by a number of agencies for tropical forest surveys using both visual and computer-assisted interpretation techniques. In some studies, coarse resolution, high temporal frequency meteorological satellite data been utilised for land cover mapping of very large areas. Radar imagery is considered to be an important source material for small-scale thematic mapping in equatorial zone because of its cloud peneteration capability. However, the coarse resolution of present generation of satellites has its obvious limitations in the near future, finer resolution data from a number of space systems are expected to provide basis for a more detailed analysis.